Peningkatan Sifat Papan Partikel Sengon dengan Perlakuan Perendaman Air Dingin (Improvement the Propoerties of Particleboard Made from Sengon with Cold Water Immersion Treatment) - Marwanto, Marwanto; Maulana, Sena; Maulana, Mohammad I; Wistara, Nyoman J; Nikmatin, Siti; Febrianto, Fauzi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
The objectives of this research is to evaluate the physical and mechanical properties of particle board made from sengon and mangium woods treated with cold water immersion. Particles of sengon and mangium immersed in cold water for 24 hours. The particles of sengon and mangium are combined with a ratio of 100: 0; 0: 100; 75:25; and 50:50. Particle boards are made in size (30x30x0,9) cm3 with target densities of 0.7 g cm-3. The particle board was binded with methylene diphenyl diisocyanate (MDI) adhesive at 10% content and hot press at 140 °C with 25 kgf cm-2 for 7 minutes. The physical and mechanical properties of particle board are evaluated according to JIS A 5908-2003 standard. The physical and mechanical properties of particle board were much affected by particle combination and cold water immersion treatment. The physical (i.e density, moisture content, water absorption (WA), and thickness swelling (TS)) and mechanical properties (ie. modulus of elasticity (MOE), modulus of rupture (MOR), and internal bonding (IB)) were evaluated. The results showed that cold water immersion improved dimensional stability (WA and TS) of particle board obtained. However, some mechanical properties decreased.Keyword: cold water immersion, mangium, particleboard, sengon